Bulk and Surface Excitons in Alloyed and Phase-Separated ZnO-MgO Particulate Systems - Zhang, Huanjun; Gheisi, Amirreza; Sternig, Andreas; Mueller, Knut; Schowalter, Marco; Rosenauer, Andreas; Diwald, Oliver; Maedler, Lutz (ACS Applied Materials and Interfaces, 2012)
The rational design of composite nanoparticles with desired optical and electronic properties requires the detailed analysis of surface and bulk contributions to the respective overall function. We use flame spray pyrolysis (FSP) to generate nanoparticles of the ternary Zn–Mg–O system the compositions of which range from solid solutions of Zn2+ ions in periclase MgO to phase separated particle mixtures which consist of periclase (cubic) MgO and wurtzite (hexagonal) ZnO phases. The structure and composition of the composite ZnxMg1–xO (0 łeq x łeq 0.3) particles are investigated using X-ray diffraction and high-resolution transmission electron microscopy, whereas UV diffuse reflectance and photoluminescence (PL) spectroscopy are used for the investigation of their optical properties. Vacuum annealing has been carried out to track the effects of stepwise elimination of surface adsorbates on the photoexcitation and PL emission properties. We demonstrate that for Zn0.1Mg0.9O particles, the admixed ZnO suppresses the MgO specific surface excitons and produces a PL emission band at 470 nm. Although gaseous oxygen partially reduces the emission intensity of hydroxylated particles, it leads to entire quenching in completely dehydroxylated samples after vacuum annealing at 1173 K. Consequently, surface hydroxyls at the solid–gas interface play a significant role as protecting groups against the PL-quenching effects of O2. The obtained results are relevant for the characterization of ZnO-based devices as well as for other metal oxide materials where the impact of the surface composition on the photoelectronic properties is usually neglected.
EAM Import::2019-03-13

Iron Precursor Decomposition in the Magnesium Combustion Flame: A New Approach for the Synthesis of Particulate Metal Oxide Nanocomposites - Gheisi, Amirreza; Niedermaier, Matthias; Tippelt, Gerold; Lottermoser, Werner; Bernardi, Johannes; Diwald, Oliver (Particle & Particle Systems Characterization, 2017)
Powders of Fe–Mg–O nanocomposite particles have been grown using a novel chemical vapor synthesis approach that employs the decomposition of a metalorganic precursor inside the metal combustion flame. After annealing in controlled gas atmospheres composition distribution functions, structure and phase stability of the obtained magnesiowüstite nanoparticles are measured with a combination of techniques such as inductively coupled plasma‐optical emission spectroscopy, energy dispersive X‐ray spectroscopy, X‐ray diffraction, and scanning and transmission electron microscopy. Complementary Mössbauer spectroscopy measurements reveal that depending on Fe loading and temperature of annealing either metastable and superparamagnetic solid solutions of Fe3+ ions in periclase (MgO) or phase separated mixtures of MgO and ferrimagnetic magnesioferrite (MgFe2O4) nanoparticles can be obtained. The described combustion technique represents a novel concept for the production of mixed metal oxide nanoparticles. Adressing the impact of selected annealing protocols, this study underlines the great potential of vapor phase grown non‐equilibrium solids, where thermal processing provides means to trigger phase separation and, concomitantly, the emergence of new magnetic propertie
Keywords: metal oxide nanoparticles; metastability; ferrimagnetism; iron admixture; phase separation; combustion synthesis

O2 adsorption dependent photoluminescence emission from metal oxide nanoparticles - Gheisi, Amirreza; Neygandhi, Chris; Sternig, Andreas; Carrasco, Esther; Marbach, Hubertus; Thomele, Daniel; Diwald, Oliver (Physical Chemistry Chemical Physics, 2014)
Optical properties of metal oxide nanoparticles are subject to synthesis related defects and impurities. Using photoluminescence spectroscopy and UV diffuse reflectance in conjunction with Auger electron spectroscopic surface analysis we investigated the effect of surface composition and oxygen adsorption on the photoluminescence properties of vapor phase grown ZnO and MgO nanoparticles. On hydroxylated MgO nanoparticles as a reference system, intense photoluminescence features exclusively originate from surface excitons, the radiative deactivation of which results in collisional quenching in an O2 atmosphere. Conversely, on as-prepared ZnO nanoparticles a broad yellow emission feature centered at h extgreeknEm = 2.1 eV exhibits an O2 induced intensity increase. Attributed to oxygen interstitials as recombination centers this enhancement effect originates from adsorbate-induced band bending, which is pertinent to the photoluminescence active region of the nanoparticles. Annealing induced trends in the optical properties of the two prototypical metal oxide nanoparticle systems, ZnO and MgO, are explained by changes in the surface composition and underline that particle surface and interface changes that result from handling and processing of nanoparticles critically affect luminescence.
EAM Import::2019-03-08

Spontaneous Growth of Magnesium Hydroxide Fibers at Ambient Conditions - Gheisi, Amirreza; Sternig, Andreas; Rangus, Mojca; Redhammer, Günther; Hartmann, Martin; Diwald, Oliver (Crystal Growth & Design, 2014)
Spontaneous transformation paths of nanomaterials point to guiding, principles for synthesis. We describe the room temperature transformation of MgO nanocubes into Mg-3(OH)(5)Cl center dot 4H(2)O nanofibers in air and investigated the underlying formation mechanism using electron microscopy, X-ray diffraction, and solid-state NMR spectroscopy. Upon contact with water vapor, the magnesium hydroxide needles were found to grow out of agglomerates of highly dispersed MgO nanocubes with preadsorbed SiCl4. Corresponding one-dimensional nanostructures do not form on low surface area materials. The presented growth approach is potentially extendable to other hydrolyzable metal oxides at ultrafine dispersion.

Stability and local environment of iron in vapor phase grown MgO nanocrystals - Niedermaier, Matthias; Dolcet, Paolo; Gheisi, Amirreza; Tippelt, Gerold; Lottermoser, Werner; Gross, Silvia; Bernardi, Johannes; Diwald, Oliver (Journal of Physical Chemistry C, 2017)
Metallocene injection into a metal combustion flame has been used for trapping transition metal ions inside MgO nanocrystals. Vacuum annealing changes the properties of resulting nonequilibrium solids toward thermodynamic equilibrium and provides means to control impurity localization and, as a result, the nanomaterials’ functional properties. By combining structure characterization (X-ray diffraction and transmission electron microscopy) with X-ray absorption spectroscopy and Mössbauer measurements, we tracked valence state and local chemical environment changes of Fe3+ ions inside vapor phase synthesized MgO nanocrystals. At a concentration of (1.5 ± 0.2) at. % Fe about (1400 ± 200) Fe3+ ions are effectively diluted within 12 nm sized nanocubes, where they form complexes between Fe3+ ions and Mg2+ vacancies. Increase of the iron concentration produces additional effects: enhanced ion diffusion and particle coarsening at elevated temperatures, clustering of Fe3+–Mg2+ vacancy complexes and, after annealing to T = 1173 K, the nucleation of a magnesioferrite phase that can be detected by X-ray diffraction for 4 at. % samples. At 3 at. % Fe, corresponding impurity ions induce surface energy changes that have a substantial impact on particle shape. With regard to the functional properties associated with transition metal ions in insulating MgO host lattices, the here presented insights underline that annealing-induced reorganization of oxide nanoparticles provides important parameters to control distribution and localization of impurity ion

Thin water films and magnesium hydroxide fiber growth - Gheisi, Amirreza; Sternig, Andreas; Redhammer, Guenther J.; Diwald, Oliver (RSC Advances, 2015)
Thin films of water covering highly dispersed metal oxides can give rise to the spontaneous and spatially controllable growth of hydroxide fibers in ambient air. Knowledge about the underlying formation mechanisms is key to the rational development of metal oxide nanomaterials and associated microstructures. We used SiCl4 as a water free chlorine ion source for the surface functionalization of MgO nanocubes and explored their subsequent transformation into magnesium oxychloride Mg3(OH)5Cl·4H2O fibers upon contact with water vapor. Specifically we show how the temperature of the functionalization process and material dispersion control the reaction pathway that can lead to very different products like Mg(OH)2, MgCl2·6H2O, or Mg3(OH)5Cl·4H2O and delineate a reaction mechanism. Lessons to be learned from this unique route to form hydroxide fibers under ambient conditions can be applied to a variety of microstructural evolution processes that involve metastable solids and superficial water acting both as a reactant and as a reaction medium for the hydration of metal oxide particle

Thin water films and particle morphology evolution in nanocrystalline MgO - Thomele, Daniel; Gheisi, Amirreza; Niedermaier, Matthias; Elsaesser, Michael S.; Bernardi, Johannes; Gronbeck, Henrik; Diwald, Oliver (Journal of the American Ceramic Society, 2018)
A key question in the field of ceramics and catalysis is how and to what extent residual water in the reactive environment of a metal oxide particle powder affects particle coarsening and morphology. With X‐ray Diffraction (XRD) and Transmission Electron Microscopy (TEM), we investigated annealing‐induced morphology changes on powders of MgO nanocubes in different gaseous H2O environments. The use of such a model system for particle powders enabled us to describe how adsorbed water that originates from short exposure to air determines the evolution of MgO grain size, morphology, and microstructure. While cubic nanoparticles with a predominant abundance of (100) surface planes retain their shape after annealing to T = 1173 K under continuous pumping with a base pressure of water p(H2O) = 10−5 mbar, higher water partial pressures promote mass transport on the surfaces and across interfaces of such particle systems. This leads to substantial growth and intergrowth of particles and simultaneously favors the formation of step edges and shallow protrusions on terraces. The mass transfer is promoted by thin films of water providing a two‐dimensional solvent for Mg2+ ion hydration. In addition, we obtained direct evidence for hydroxylation‐induced stabilization of (110) faces and step edges of the grain surface
Keywords: interfaces; magnesium oxide; coarsening; grain growth